2006
DOI: 10.1186/1478-4491-4-10
|View full text |Cite
|
Sign up to set email alerts
|

The training and development needs of nurses in Indonesia: paper 3 of 3

Abstract: Background: Indonesia's recent economic and political history has left a legacy of widespread poverty and serious health problems, and has contributed to marked inequalities in health care. One means of responding to these challenges has been through a reconsideration of the professional roles of nurses, to enable them to deal with the range and complexity of health problems. However, there are currently a number of obstacles to achieving these aims: there is a serious shortfall in trained nurses; the majority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
2
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 8 publications
1
41
2
2
Order By: Relevance
“…They found that all nurses reported significant training needs for all 40 tasks. [24] Also, these results disagree with Jones (2008), about training needs of nurses working in child and adolescent services. He found that training needs varied depending on the career trajectory of nurses, and where nurses were working.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…They found that all nurses reported significant training needs for all 40 tasks. [24] Also, these results disagree with Jones (2008), about training needs of nurses working in child and adolescent services. He found that training needs varied depending on the career trajectory of nurses, and where nurses were working.…”
Section: Discussioncontrasting
confidence: 55%
“…[22,23] It is obvious from the present study that the nurses needs for theoretical knowledge and training skills were low. These results disagree with Hennessy et al (2006), who assess the training and development needs of nurses in Indonesia. They found that all nurses reported significant training needs for all 40 tasks.…”
Section: Discussioncontrasting
confidence: 51%
“…Approximately 6.3 million perinatal deaths and 500,000 maternal deaths occur annually all over the world with 99% occurring in the developing countries and are avoidable [12]. According to World Health Organization [12], most of the interventions aiming at reducing perinatal and maternal mortalities need a responsive health system. A responsive health system is one offering appropriate antenatal care; comprehensive emergency obstetrics care and quality delivery services.…”
Section: Introductionmentioning
confidence: 99%
“…"It is any planned series of incidents at any time in the life span, having a humanistic basis directed towards the participants learning and understanding" [11]. Approximately 6.3 million perinatal deaths and 500,000 maternal deaths occur annually all over the world with 99% occurring in the developing countries and are avoidable [12]. According to World Health Organization [12], most of the interventions aiming at reducing perinatal and maternal mortalities need a responsive health system.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the quality of nursing care for sick children with ARI in Indonesia is still far from optimal. This is due to the lack of regulatory standards for education and clinical competence, the absence of proper job descriptions, and also, the training of many nurses does not necessarily match the nature of the work being undertaken (Hennessy, Hicks, Hilan & Kowanal 2006). Chakraborty and Frick (2002) conducted a study among private hospitals in rural West Bengal, India and focused on providers' disease management practices for acute respiratory infections among under-five children.…”
Section: Introductionmentioning
confidence: 99%